Produktivitas Alat Berat Pengecoran Kolom pada Pembangunan Apartemen 31 Sudirman Suites Makassar - Fedelia Randan; Junus Mara; Lintje Tammu Tangdialla (Paulus Civil Engineering Journal, 2021)
In the world of heavy equipment construction projects it is important to help complete human work. Tower Crane is one of the tools in the implementation of construction projects. In the implementation of the construction of Apartment 31 Sudirman Suites Makassar, there are 2 Tower Crane tools that operate with limited work time due to covid 19. This research was carried out by direct observation in the field and calculating the real value of the specifications to compare productivity. Tower Crane productivity is the result achieved or output, namely the amount of material moved by Tower Crane with all resources or inputs, namely the time required for material transfer. Based on the calculation results that the productivity of the specification is greater than the productivity of observations in the field, this is due to constraints on the weather that occurs and the equipment operator. For productivity, the average obtained on the 4th floor is 71,544 (%) and on the 5th floor it is obtained that is 73,727 (%).